Chikungunya Virus in US Travelers Returning from India, 2006 - Lanciotti, Robert S.; Kosoy, Olga L.; Laven, Janeen J.; Panella, Amanda J.; Velez, Jason O.; Lambert, Amy J.; Campbell, Grant L. (Emerging infectious diseases, 2007)
Chikungunya virus (CHIKV), a mosquito-borne alphavirus, is endemic in Africa and Asia. In 2005-2006, CHIKV epidemics were reported in islands in the Indian Ocean and in southern India. We present data on laboratory-confirmed CHIKV infections among travelers returning from India to the United States during 2006.